RETRACTED: Icariin Reduces Dopaminergic Neuronal Loss and Microglia-Mediated Inflammation in Vivo and in Vitro - Wang, Guo-Qing; Li, Dai-Di; Huang, Chun; Lu, Di-Sheng; Zhang, Chao; Zhou, Shao-Yu; Liu, Jie; Zhang, Feng (Frontiers in Molecular Neuroscience, 2018)
Parkinson’s disease (PD) is one of the most common neurodegenerative diseases characterized with a gradual loss of midbrain substantia nigra (SN) dopamine (DA) neurons. An excessive evidence demonstrated that microglia-mediated inflammation might be involved in the pathogenesis of PD. Thus, inhibition of neuroinflammation might possess a promising potential for PD treatment. Icariin (ICA), a single active component extracted from the Herba Epimedii, presents amounts of pharmacological properties, such as anti-inflammation, anti-oxidant, and anti-aging. Recent studies show ICA produced neuroprotection against brain dysfunction. However, the mechanisms underlying ICA-exerted neuroprotection are fully illuminated. In the present study, two different neurotoxins of 6-hydroxydopamine (6-OHDA) and lipopolysaccharide (LPS)-induced rat midbrain DA neuronal damage were applied to investigate the neuroprotective effects of ICA. In addition, primary rat midbrain neuron-glia co-cultures were performed to explore the mechanisms underlying ICA-mediated DA neuroprotection. In vitro data showed that ICA protected DA neurons from LPS/6-OHDA-induced DA neuronal damage and inhibited microglia activation and pro-inflammatory factors production via the suppression of nuclear factor-κB (NF-κB) pathway activation. In animal results, ICA significantly reduced microglia activation and significantly attenuated LPS/6-OHDA-induced DA neuronal loss and subsequent animal behavior changes. Together, ICA could protect DA neurons against LPS- and 6-OHDA-induced neurotoxicity both in vivo and in vitro. These actions might be closely associated with the inhibition of microglia-mediated neuroinflammation.